Avaliação da atenção nutricional no âmbito dos núcleos de apoio à saúde da família no Brasil - Araújo, Thaise Anataly Maria de (2018)
The Unified Health System (SUS, in portuguese) emerged amidst the political and social movements of Brazil. One of its components, Basic Care (AB), includes the Family Health Strategy (ESF), whose Family Health Support Centers (NASF) are linked and have, among their actions, nutritional care - AN. The National Program for Improving Access and Quality of Basic Care (PMAQ – AB), established in 2011, has External Evaluation (AE) as one of its phases, and its results can reorient health actions. This research aims to evaluate A within the scope of the NASF throughout Brazil, from the AE of the PMAQ – AB. This is a cross-sectional and analytical study, with a quantitative approach and a secondary basis. It consisted of seven steps, composed of statistical analyzes (descriptive analysis, Pearson's chi-square test and binary logistic regression). The AE questions related to the AN axis constituted the dependent variables, while the independent ones covered the other axes, selected after each methodological step. We disregarded the models with low determination coefficients and the independent variables omitted in the regression. The results are exposed under measures of effect (Odss Ratio - OR). Among the main findings, NASF support to the development of Food and Nutrition Surveillance (VAN) actions was favored by the provision of a shared office (OR = 0,704), analysis of the number of erroneous or unnecessary referrals for specialized care ( OR = 0,749) and monitoring of follow-up users at other points of attention (OR = 0.749). The least contributory aspect of VAN's actions was support to the provision of care for people with chronic diseases (OR = 6,431), who also competed with actions to Promote Adequate and Healthy Food (PAAS) (OR = 4,634); diseases related to food and nutrition (OR = 3.862) and to the intersectoral articulation, to guarantee Food and Nutritional Security – SAN (OR = 3.722). The qualification of referrals to other points of attention was the one that most strengthened the effectiveness of PAAS actions (OR = 0.679). The accomplishment of family orientations optimized the development of actions directed to the aggravations related to the feeding and nutrition (OR = 0,497). Concerning the actions of intersectoral articulation, in order to guarantee SAN, the following elements were highlighted: the existence of schedules or scales of use of the rooms (OR = 0,726), analysis of health indicators of the population of the territory (OR = 0,706) and monitoring of users at other points of attention (OR = 0,787). Through the external evaluation of the PMAQ – AB, it is inferred that the AN strengthened within the AB scope, mediated by the NASF professionals. However, and in line with its guidelines, it is still necessary to strengthen intersectoriality, articulation among NASF professionals, Family Health teams and users, as well as the training focused on SUS and the implementation of Permanent Education. This study can stimulate the analysis of new cycles of the PMAQ – AB, making possible the comparison of the results and fomentation to the strategic planning in health.